Prokaryotic assemblages within permafrost active layer at Edmonson Point (Northern Victoria Land, Antarctica). (August 2018) - Papale, Maria; Conte, Antonella; Mikkonen, Anu; Michaud, Luigi; La Ferla, Rosabruna; Azzaro, Maurizio; Caruso, Gabriella; Paranhos, Rodolfo; Cabral Anderson, S.; Maimone, Giovanna; Rappazzo, Alessandro Ciro; Rizzo, Carmen; et al.
Abstract: This study was aimed at gaining insights on the prokaryotic community (in terms of both taxonomic composition and activities) inhabiting the active layer at Edmonson Point, an ice-free area on the eastern slope at the foot of Mount Melbourne (Northern Victoria Land, Antarctica). Samples were collected during the thawing period, when microbial physiological activities are restored to utilize previously frozen organic substrates. Despite the very small cell sizes (<0.1 μm 3 ), indicating the occurrence of stressed, dormant and/or starved cells, the prokaryotic communities appeared to be metabolically active in the decomposition of high molecular weight (>600 Da) substrates, as indicated also by the obtained rates of enzymatic hydrolytic activities over proteolytic, glycolitic and phosphoric compounds. Taxonomical composition showed that Proteobacteria, Actinobacteria and Firmicutes dominated the prokaryotic community, with most of their members playing crucial roles in organic matter turnover, as well as nitrogen cycling, or entering a viable but not cultivable state to cope with continuously changing environmental conditions, such as in the case of the active layer. Finally, non-autochthonous bacteria (mainly of marine origin) were detected and they probably contribute to the organic matter turnover within such cold terrestrial habitat. This research provides the first comprehensive account of the prokaryotic communities inhabiting the Antarctic permafrost and contributes to existing information on the response of their abundance and metabolism in a permafrost area that undergoes to seasonal changes (e.g. in terms of temperature, water availability and ice presence). Highlights: Nitrogen- and CO2 -fixing bacteria are found in the Edmonson Point active layer. Prokaryotic community is able to degrade high molecular weight compounds. Enzymatic assays show a metabolically active microbial community. Stressed, starved and dormant cells (sizes smaller than 0.1 μm 3 ) are also found.